Leuctra pinhoti, a new species of stonefly (Plecoptera: Leuctridae) from Alabama, U.S.A. - Grubbs, Scott A. (Illiesia, 2009)
Leuctra pinhoti sp. n. is described from the Talladega National Forest region of eastern Alabama, U.S.A. Leuctra pinhoti sp. n. is distinguished from other members of the L. biloba species group mainly by the unique dorsal process on the male 8th abdominal tergum. A new Alabama state record of Diploperla robusta Stark & Gaufin is reported.
Keywords: entomology; vrbnice; new species; entomologija; nove vrste; Plecoptera; Leuctridae; Leuctra; Alabama